VD_FINDINFO HC / 2016 / 63 vom 21. Dezember 2015 - VD Tribunal cantonal (2015)
ENFANT, REVENU HYPOTHÉTIQUE, ACTION EN PAIEMENT D'ENTRETIEN, MESURE PROVISIONNELLE | 276 al. 1 CC, 277 al. 2 CC, 285 al. 1 CC, 302 al. 2 CC, 261 al. 1 CPC (CH)